Students’ Perceptions of Interfaith Tolerance as a Key to Harmony in Campus Life - Yasin Azhari; M. Rizky Akbar Alfarizi; Ferry Ardiansyah; Sheva Yudha Pratama (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study seeks to explore students’ perceptions of interfaith tolerance within campus life, with a particular focus on second-semester students at Bhakti Kartini Polytechnic. Campus life is often regarded as a microcosm of a multicultural society and thus serves as a strategic arena for nurturing values of tolerance and interreligious harmony. Employing a qualitative descriptive approach, data were collected through questionnaires and semi-structured interviews with 20 respondents representing diverse religious backgrounds. The findings reveal that students generally hold a positive perception of tolerance, viewing it as a fundamental principle for fostering peaceful and harmonious interactions on campus. These results are consistent with previous research, which underscores the significant role of tolerance education in shaping inclusive, cohesive, and productive social environments.